Japan in Transition: From Tokugawa to Meiji - MARIUS B. JANSEN, GILBERT ROZMAN (Princeton University Press, 2014)
This is a book about the changeover from Tokugawa (1600-1868) to Meiji (1868-1912) in nineteenth-century Japan. It was a transition from early modern (kinsei) to modern (kindai), as the Japanese put it; from late-feudal to modern institutions, as many historians have described it, from shogunal to imperial rule, and from isolation to integration in the world economy. Most accounts treat it chiefly in its political dimension, focusing on the events associated with the return of power to the throne. The Meiji Restoration, the central event of that transition, thus serves as its symbol. Too frequently it also serves to shield the student from the longer and deeper process of revolutionary social change that was underway and that gave the Restoration its significance in world history. In their totality, the changes with which these chapters are concerned constituted a profound transformation of Japanese society. But it was one long in taking shape, and its future outlines were never as clear to those who led as their subsequent recollections seemed to indicate. It is easy to be taken in by the rhetoric of the Meiji leaders, most of it produced long after the state had taken form—a rhetoric that implies an unchanging vision and a steady purpose. In fact, vision and purpose were in process of definition throughout the period of transition. The general outlines of a country that would be able to compete with other countries were in the leaders' minds, but the shape and individuality of its institutions—even its political institutions—were in question for several decades. Kido Takayoshi's discovery of the uses of the 1868 Charter Oath during his visit to Washington in 1872 provides a case in point. Later generations would point to that document as a blueprint, and in recent years it has even been credited with containing the germ of the liberal Constitution of 1947; but at the time it was issued, as Michio Umegaki shows in Chapter 4, the Oath was designed as reassurance for daimyo and leading samurai. Even Kido, who had contributed to its formulation, was startled by his realization of its future utility.